1992
DOI: 10.1152/ajprenal.1992.262.2.f217
|View full text |Cite
|
Sign up to set email alerts
|

Localization of ecto-ATPase in rat kidney and isolated renal cortical membrane vesicles

Abstract: Brush-border (BBMV) and basolateral membrane vesicles (BLMV) from rat renal cortex exhibit an ecto-ATPase activity that is distinct from other ATPases. We have examined the cellular and regional distribution of this enzyme in rat kidney using antibodies against rat liver ecto-ATPase. In isolated vesicles, the distribution shown by biochemical assays of ATPase activity was confirmed by immunocytochemistry and Western blotting. Indirect immunofluorescence and immunogold labeling showed that brush borders of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 16 publications
1
32
0
Order By: Relevance
“…Previous studies showed localization of CAM105 in the BBM of S1 and S3, but not S2 segments of the rat kidney proximal tubules, and also in the plasma membrane of peritubular capillaries (Sabolić et al, 1992a). The present study was performed on cryosection of the kidney cortex, thus showing the protein expression in proximal tubule S1 segments and peritubular capillaries ( Fig.…”
Section: Cam105supporting
confidence: 56%
See 2 more Smart Citations
“…Previous studies showed localization of CAM105 in the BBM of S1 and S3, but not S2 segments of the rat kidney proximal tubules, and also in the plasma membrane of peritubular capillaries (Sabolić et al, 1992a). The present study was performed on cryosection of the kidney cortex, thus showing the protein expression in proximal tubule S1 segments and peritubular capillaries ( Fig.…”
Section: Cam105supporting
confidence: 56%
“…The commercial antibodies against the following proteins were used: Na/KATPase (monoclonal anti-peptide antibody against the α1 subunit of the human protein, Santa Cruz Biotechnology, CA, USA), metallothionein (monoclonal antibody against the polymerized MT1 and MT2 horse holoproteins; Dako North America, CA, USA), actin (monoclonal anti-peptide antibody; Millipore, MA, USA), and α-tubulin (monoclonal antibody against the see urchin filament; Sigma, MO, USA). The non-commercial antibodies against the following proteins were used: megalin (polyclonal antibody against the rat holoprotein; characterized in Abbate et al, 1994 andSabolić et al, 2002), CAM105 (polyclonal antibody against the rat holoprotein; characterized in Sabolić et al, 1992a), AQP1; polyclonal antibody against the rat holoprotein; characterized in Sabolić et al, 1992b), and V-ATPase (polyclonal anti-peptide antibody against the 31 kDa ("E") subunit;…”
Section: Antibodies and Other Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…These membranebound enzymes with their ATP hydrolyzing site on the extracellular surface have been found on a wide range of cell types and membrane preparations, including cholinergic nerve terminals (Zimmermann et al, 1986) endothelial cells (see Gordon, 1986, for review), renal cortical membrane vesicles (Sabolic et al, 1992) hepatocytes (Lin, 1989) and smooth muscle cells (see Cusack et al, 1988, for review). In conjunction with other ectonucleotidases, ecto-ATPases are responsible for initiating the complete hydrolysis of ATP to adenosine (Zimmermann et al, 1986), but are not associated with membrane transport (Lin, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Ab-I detected a doublet band of an approximate molecular mass of > 90 kD in both membrane fractions. A recent report by Sabolic et al ( 18) using rat BBM and BLM indicates that both membrane preparations may be contaminated with endothelial cell membranes.…”
Section: Discussionmentioning
confidence: 99%